Relative deprivation, inequality and the Covid-19 pandemic. (May 2023) - Chakrabarty, Debajyoti; Bhatia, Bhanu; Jayasinghe, Maneka; Low, David
Abstract: There is a growing concern that inequalities are hindering health outcomes. This paper's primary objective is to investigate the role of relative deprivation and inequality in explaining the daily spread of the Covid-19 pandemic. For this purpose, we use secondary cross-sectional data across 119 (developed and developing) countries from January 2020 – to April 2021. For the empirical analysis, we use a recent dynamic panel data modelling approach that allows us to identify the role of time-invariant variables such as degree of globalisation, political freedom and income inequality on the dynamics of the pandemic and fatality rates across countries. We find that new cases per million and fatality rates are highly persistent processes. After controlling for time-varying mobility statistics from the Google mobility database and region-specific dummy variables, the two significant factors that explain the severity of Covid-19 spread in a country are per-capita Gross Domestic Product (GDP) and Yitzhaki's relative income deprivation index. Lagged value of new cases per million significantly explains cross-country variations in the daily case fatality rates. A higher proportion of the older population and pollution increased fatality rates while better medical infrastructure reduced it. Highlights: Higher inequality led to a faster spread of Covid-19 cases. Per-capita GDP has a positive and significant effect on Covid-19 cases. Google mobility data is a good predictor of Covid-19 cases. Faster spread of Covid-19 cases is associated with higher case fatality rates. Pollution increased Covid-19 fatality rates.